#ICAREFORHER INTER-CHARITIES BUBBLE & SPLASH 5KM RUN – ALL USM STUDENTS ARE INVITED! - MPRC, Pusat Media & Perhubungan Awam (2017)
MMICARE Association in collaboration with AsiaPacific UniversityCommunity Engagement Network (APUCEN), Division of Industry and Community Network (BJIM), Universiti Sains Malaysia (USM) and the organisers of Miss Malaysia Indian Global Personal Empowerment Programme for girls will be organising the #ICAREFORHER InterCharities Bubble & Splash 5KM.